2003
DOI: 10.1001/archfaci.5.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip Nasal Reconstruction Using Porous High-Density Polyethylene

Abstract: Background: The multitude of factors involved with a unilateral cleft lip nasal defect has spurred various surgical techniques in the past. Recently, synthetic materials have been introduced for use in nasal reconstruction. Objective: To report on and illustrate the use of porous high-density polyethylene implants in cleft lip nasal reconstruction. Design: A retrospective review of cleft lip nasal reconstruction using porous high-density polyethylene in pa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…A previous study reported 5 cases of infection in 121 cases of high-density porous polyethylene implant rhinoplasty, and no other complications, such as extrusion or exposure, were found. 23,24 As in previous studies, no other complications were found in our other patients. Romano et al 22 and Merritt et al 25 have reported that vascularized tissue ingrowth reduces the infection of high-density porous polyethylene implants and also prevents dislocation and extrusion.…”
Section: Resultssupporting
confidence: 84%
“…A previous study reported 5 cases of infection in 121 cases of high-density porous polyethylene implant rhinoplasty, and no other complications, such as extrusion or exposure, were found. 23,24 As in previous studies, no other complications were found in our other patients. Romano et al 22 and Merritt et al 25 have reported that vascularized tissue ingrowth reduces the infection of high-density porous polyethylene implants and also prevents dislocation and extrusion.…”
Section: Resultssupporting
confidence: 84%
“…All of our patients had no infection occurred. It was complete opposite when using synthetic implant, it may lead to implant infection or protusion, as Romo 9 reported in his study with 18 patients with cleft nose; one (6%) patient had an infection 6 months after the procedure that required intravenous antibiotics and implant removal. The soft tissue in radix area is very thin, if the infection occurred, it might complicate further revision surgery since the soft tissue there remains little.…”
Section: Discussion T H E M O S T C O M M O N N O E F R a C T U R E Cmentioning
confidence: 88%
“… 6 The infection rate in our patient population using this technique is around 7.7%, and all cases of infection resolved with the use of oral antibiotics. 7 Romo et al 8 reported the use of porous high-density polyethylene implants for cleft lip nasal reconstruction with a low infection rate of 6%. However, infection of the porous high-density polyethylene implant usually requires intravenous antibiotic treatment and implant removal.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue ingrowth in the implant might complicate the implant removal, especially in patients with thin skin in the radix area. 8 …”
Section: Discussionmentioning
confidence: 99%